Distribution of Rare Earth Elements in the Metamorphic Rocks of the Paleoproterozoic Nyong Unit (Congo Craton, South – Cameroon) - NDEMA MBONGUE, JEAN-LAVENIR; Sigué, Cyrille; NZENTI, JEAN PAUL; Cheo , Emmanuel Suh Cheo (IJRDO-Journal of Applied Science, 2019)
We reported for the first time the geochemistry of rare earth elements (REE) for the metamorphic rocks of the Paleoproterozoic Nyong unit situated at the west of Congo craton in Cameroon. Rare earth elements, define a group of fifteen chemical elements from lanthanum to lutetium (atomic numbers 57-71) characterized by similar chemical properties. To study their distribution in the metamorphic rocks of the Nyong unit, 24 representative samples were selected. The selected samples were analyzed by inductively coupled plasma mass spectrometry (ICP-MS). Rocks are strongly enriched in REE (especially LREE) and these rare earths set up a complex group. The abundance of REE suggests the presence of REE-rich minerals such as monazite and this monazite should be rich in LREE (La, Ce, Nd, Sm). The variations of the REE fractionation in the studied rocks is explained by different degrees of partial melting of the protolith and by variable enrichment of the source. REE concentrations in the rocks were of geogenic origins and not influenced by anthropogenic sources. LREE enrichment result in geochemical distribution of these elements in the area and good correlation between them. The unusually high contents of REE and unusually high contents of light rare earths enrichment compared to heavy rare earths is highlighted in biotite-gneisses, garnet-micaschists and garnet charnockitic gneisses. Chondrite normalization patterns are parallel; they show high LaN/YbN ratios which reflect highly fractioned REE compositions displaying a W-profile and a strong Eu anomaly for meta-igneous unit; zigzag-profile with a marked negative Ce anomaly and a pronounced positive Eu anomaly for metasediments. REE residence includes major minerals (feldspar, garnet, amphibole, biotites, clinopyroxene, epidote) and accessory minerals (phosphates such as monazite). The REE of Edea region can be economically exploitable.